2010
DOI: 10.1108/09578231011079584
|View full text |Cite
|
Sign up to set email alerts
|

The lived experiences of female educational leadership doctoral students

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Malone et al (2004) documented gender differences in the field of educational administration in terms of employment and career, indicating that male and female doctoral students bring different needs, aspirations, and expectations at the entry of their programs. Even though gender has not emerged as a statistically significant predictor of doctoral degree completion, many researchers have documented the unique challenges and barriers of female doctoral students in completing their doctoral programs (e.g., Maher, Ford, & Thompson, 2004;Manfield, Welton, Lee, & Young, 2010;Moyer, Salovey, & Casey-Cannon, 1999). These challenges have included greater work demand, financial constraints, child-care responsibilities, and low level of confidence (Maher et al, 2004;Manfield et al, 2010;Moyer et al, 1999).…”
Section: Gender Grade Point Average and Doctoral Degree Completionmentioning
confidence: 99%
“…Malone et al (2004) documented gender differences in the field of educational administration in terms of employment and career, indicating that male and female doctoral students bring different needs, aspirations, and expectations at the entry of their programs. Even though gender has not emerged as a statistically significant predictor of doctoral degree completion, many researchers have documented the unique challenges and barriers of female doctoral students in completing their doctoral programs (e.g., Maher, Ford, & Thompson, 2004;Manfield, Welton, Lee, & Young, 2010;Moyer, Salovey, & Casey-Cannon, 1999). These challenges have included greater work demand, financial constraints, child-care responsibilities, and low level of confidence (Maher et al, 2004;Manfield et al, 2010;Moyer et al, 1999).…”
Section: Gender Grade Point Average and Doctoral Degree Completionmentioning
confidence: 99%
“…We found only two studies involving mentorship of students for the educational leadership professoriate, and each had a gendered perspective. In research by Mansfield et al (2010), only 2 of 12 female participants reported having strong professor-student mentoring relationships, and 9 desired substantial improvements in mentoring quality. Mentoring was more likely to emerge out of informal relationships, and some students struggled to form these relationships.…”
Section: Mentoring Within Higher Education and Educational Leadershipmentioning
confidence: 92%
“…High-quality graduate student mentoring experiences are uncommon (Mullen, 2009) and research addressing mentorship for the professoriate is scarce (Mansfield, Welton, Lee, & Young, 2010). Thus, the issues described previously-relating to mentoring research in general-are especially pronounced within this subset of the literature.…”
Section: Mentoring Within Higher Education and Educational Leadershipmentioning
confidence: 94%
“…Informed by FST, Mansfield, Welton, Lee, and Young (2010) sought to understand the challenges and opportunities of women doctoral students in educational leadership departments. A qualitative questionnaire and a collaborative focus group consisting of 12 women representing a variety of demographic characteristics (i.e., one Black, two Asian, two Latinas, one multiracial, and six White) were surveyed to explore participants' experiences and perceptions with the intent of revealing strategies to support the success of women doctoral students.…”
Section: Feminist Standpoint Theorymentioning
confidence: 99%
“…A qualitative questionnaire and a collaborative focus group consisting of 12 women representing a variety of demographic characteristics (i.e., one Black, two Asian, two Latinas, one multiracial, and six White) were surveyed to explore participants' experiences and perceptions with the intent of revealing strategies to support the success of women doctoral students. Limitations within the organizational culture (i.e., confusion about access to professional networks within the academic community); personal and family sacrifices (i.e., the stress of work and school time constraints exacerbated time for familial life); identity issues (i.e., race, ethnicity, age, social class, language, and immigrant status added complexity to the doctoral experience); self-doubts, and mentoring experiences emerged as themes from the participants' perceptions (Mansfield et al, 2010). These findings have important implications for designing doctoral programs that explicitly identify and address disparities in access to professional networks for women within the academic organization.…”
Section: Feminist Standpoint Theorymentioning
confidence: 99%